2015
DOI: 10.3390/biom5020435
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Alpha-Synuclein Clearance and Spreading

Abstract: Abstract:Parkinson's Disease (PD) is a complex neurodegenerative disorder classically characterized by movement impairment. Pathologically, the most striking features of PD are the loss of dopaminergic neurons and the presence of intraneuronal protein inclusions primarily composed of alpha-synuclein (Į-syn) that are known as Lewy bodies and Lewy neurites in surviving neurons. Though the mechanisms underlying the progression of PD pathology are unclear, accumulating evidence suggests a prion-like spreading of Į… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 277 publications
3
67
0
Order By: Relevance
“…VH14 would be expected to bind primarily to the monomeric form of α-Syn, since the NAC region may be rapidly bound in homo or heterologous multimers, with the epitope buried internally and inaccessible to the nanobody [7]. Clearance of higher order structures of α-Syn have been shown to require autophagy [46]. A recent publication showed that relative concentrations of the different forms of α-Syn, including extracellular forms of the monomer, may play important roles in PD [47].…”
Section: Discussionmentioning
confidence: 99%
“…VH14 would be expected to bind primarily to the monomeric form of α-Syn, since the NAC region may be rapidly bound in homo or heterologous multimers, with the epitope buried internally and inaccessible to the nanobody [7]. Clearance of higher order structures of α-Syn have been shown to require autophagy [46]. A recent publication showed that relative concentrations of the different forms of α-Syn, including extracellular forms of the monomer, may play important roles in PD [47].…”
Section: Discussionmentioning
confidence: 99%
“…Intravesicular pH drops along the endocytic pathway to ϳ6 and in late endosomes and lysosomes to as low as 4.5 (25,27). In addition to its role in vesicular fusion and trafficking, ␣S is subject to lysosomal degradation (28), and it may enter the slightly alkaline mitochondrial environment (29). Furthermore, pH dysregulation accompanying oxidative stress can result in cytosolic acidification (30), and oxidative stress is a significant contributor to PD pathology (31).…”
mentioning
confidence: 99%
“…Here, we show evidence ( Figure 6) that OPTN localization with alpha-synuclein positive intracellular puncta are increasingly evident in rotenone treated animals. Given that alpha-synuclein can be degraded by the ubiquitinproteasome pathway, chaperone mediated autophagy, and macroautophagy, targeted studies will be required to understand OPTN and alpha-synuclein interactions (Lopes da Fonseca et al, 2015). Mechanistic in vitro studies will need to be conducted in the future to confirm and understand the role of OPTN in mediating aberrant autophagy and PD-relevant neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%